Propofol-Related Infusion Syndrome in the Peripartum Period - Akwugo A. Eziefule; Solafa Elshatanoufy; Mili Thakur; Frederico G. Rocha (Thieme Medical Publishers, Inc., 2016)
Abstract Background Propofol is a widely known, commonly used drug. Complications can occur with the use of this drug, including propofol-related infusion syndrome (PRIS). PRIS, in the obstetric population, has not been documented; however, we report a case of a patient who developed PRIS after an emergent cesarean delivery of a preterm infant. Case Study A 35-year-old multigravida woman presented complaining of leakage of fluid and decreased fetal movement. Her pregnancy was complicated by methadone maintenance therapy due to a history of opioid abuse. Complications after admission for prolonged monitoring and a prolonged fetal heart tone deceleration was noted with no recovery despite intrauterine resuscitation. An emergent cesarean delivery was performed using general anesthesia and endotracheal intubation after which she developed aspiration pneumonia. She was admitted to the intensive care unit and reintubation and sedation were required secondary to respiratory distress. Sedation was achieved using propofol infusion. She subsequently developed changes in her electrocardiogram, an increase of her serum creatinine, creatinine protein kinase, lipase, amylase, and triglycerides, making the diagnosis of PRIS. Conclusion PRIS should be included in the differential diagnosis of intubated or postoperative patients in the obstetric population.